Polyurethane Insulation Foams for Energy and Sustainability - Burgaz, Engin (Advanced Structured Materials,, 2019)
This review book focuses on the structure-property relationships of polyurethane nanocomposite foams in comparison with those of conventional polyurethane composite foams. The thermal insulation properties of polyurethane foam nanocomposites are discussed along with other traits such as their morphology, mechanical and thermomechanical properties, thermal degradation and flammability, energy absorption and saving capability, recycling and recovery behavior. In turn, the book discusses potential applications of PU nanocomposite foams and outlines the main problems that remain to be solved with regard to this important topic.